Sistema web de gestión documental para la mejora continua del sistema integrado de gestión de La Empresa Corps Safety & Security s.a.c. - Horna Amambal, Percy José (2019)
The present work is titled “Sistema Web de Gestión Documental Para la Mejora Continua del Sistema Integrado de Gestión de la Empresa Corps Safety & Security S.A.C”. One of the main objectives is the access to the documentation and information of the Integrated Management System in a fast, efficient and avoiding the use of obsolete documents, from the place where the user is either through a computer or a Smartphone. The implementation of the Document Management Web System was successfully accomplished using the XP methodology, using the programming languages: PHP and HTML for web content and MySql for database management. The Object Orientation paradigm was followed and for the database model, the principles of normalization and the entity - relationship models were used. The perspective of the work carried out is to keep updated documentation in the operational units where the service is provided, to contribute with the continuous improvement of the Integrated Management System of the company Corps Safety & Security S.A.C. from the city of Lima and provide documentation and information to administrative and operational staff to offer a quality service to our customers.